2015
DOI: 10.1017/s0033291715001373
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of metamemory functioning in the at-risk mental state for psychosis

Abstract: These data underline the presence of a metamemory bias in ARMS patients which is even more pronounced in FEP patients. The bias might represent an early cognitive marker of the beginning psychotic state. Longitudinal studies are needed to unravel whether metacognitive deficits predict the transition to psychosis and to evaluate therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 54 publications
2
35
0
4
Order By: Relevance
“…Therefore, this review focuses on CL ratings as a measure of metamemory ability. CL ratings have been assessed in a variety of tasks, for example verbal recognition tasks (Kircher et al, 2007), verbal (Moritz et al, 2004; Laws and Bhatt, 2005; Bhatt et al, 2010; Eifler et al, 2015; Eisenacher et al, 2015; Hodgetts et al, 2015) or visual (Moritz et al, 2008; Peters et al, 2012, 2013) false memory tasks, source monitoring tasks (Moritz and Woodward, 2002, 2006a,b; Moritz et al, 2003, 2005; Doré et al, 2007; Garcia et al, 2012) or general knowledge tasks (Bacon et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this review focuses on CL ratings as a measure of metamemory ability. CL ratings have been assessed in a variety of tasks, for example verbal recognition tasks (Kircher et al, 2007), verbal (Moritz et al, 2004; Laws and Bhatt, 2005; Bhatt et al, 2010; Eifler et al, 2015; Eisenacher et al, 2015; Hodgetts et al, 2015) or visual (Moritz et al, 2008; Peters et al, 2012, 2013) false memory tasks, source monitoring tasks (Moritz and Woodward, 2002, 2006a,b; Moritz et al, 2003, 2005; Doré et al, 2007; Garcia et al, 2012) or general knowledge tasks (Bacon et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The importance of metamemory functioning to schizophrenia lies not only in its potential mode of action within the development and maintenance of positive symptoms (Eifler et al, 2015; Eisenacher et al, 2015) but also in its relevance to psychosocial functioning (Scheyer et al, 2014). It is assumed that biases in metamemory are associated with a stronger severity of positive symptoms, particularly with delusions (Moritz and Woodward, 2006a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Überkonfi-denz in Fehlurteile, gepaart mit der niedrigen Konfidenz bei richtigen Urteilen, führt zu «Wissenskontamination» (definiert als das Verhältnis von hochkonfidenten falschen Antworten zu allen hochkonfidenten Antworten). Überkonfidenz für Fehlurteile wurde auch bei ersterkrankten schizophrenen Patienten [Moritz et al, 2006b;Woodward et al, 2006] sowie bei Hochrisiko-Personen festgestellt und manifestiert sich somit nicht nur in der akuten Psychose [Eisenacher et al, 2015;Moritz et al, 2015a].…”
Section: Empirische Fundierungunclassified
“…Based on previous work showing similar patterns of cognitive impairment between FE and chronically ill patients (Lewandowski et al 2011), we predicted that the FE group would show prominent relational and recollective memory impairments, and moderate item and familiarity memory impairments compared to typically developing (TD) individuals. Previous CHR research found intermediate level impairments on measures of verbal memory (Hou et al, 2016, Liu et al, 2015), meta-memory (Eisenacher et al, 2015), working memory (Goghari et al, 2014), and declarative memory (see Cirillo et al, 2003 for review). Therefore, we expected the CHR group to show better performance than the FE group, but worse performance relative to TD individuals.…”
Section: Introductionmentioning
confidence: 97%